Teachers' perception of gender on gender-responsive learning in the vocational school of tourism - Wijanarko, Setiawan; Nurlaela, Luthfiyah; Maspiyah, Maspiyah; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2022)
This study aims to determine the teacher's perception of gender towards gender-responsive learning. This research with a quantitative approach uses a questionnaire data collection method (questionnaire) consisting of a questionnaire on teacher perceptions of gender, teacher attitudes towards students, interaction in learning, and gender-responsive learning. The questionnaire uses a Likert scale with four answer choices. From the results of the calculation of the data, it can be seen that the mean value of teachers' perceptions of gender at SMK Negeri 8 Surabaya is 84.87 in the 76-90 interval which means that teachers' perceptions of gender towards responsive Hender learning are classified as "good". In this case, the teacher's perception of gender at SMK Negeri 8 Surabaya can influence well, providing equality in access, control, participation, and benefits for male and female students in a balanced way.